The Microbiome as a Key Regulator of Female Genital Tract Barrier Function - Plesniarski, Andrew; Siddik, Abu Bakar; Su, Ruey-Chyi (Frontiers in Cellular and Infection Microbiology, 2021)
The microbiome, the collection of microbial species at a site or compartment, has been an underappreciated realm of human health up until the last decade. Mounting evidence suggests the microbiome has a critical role in regulating the female genital tract (FGT) mucosa’s function as a barrier against sexually transmitted infections (STIs) and pathogens. In this review, we provide the most recent experimental systems and studies for analyzing the interplay between the microbiome and host cells and soluble factors with an influence on barrier function. Key components, such as microbial diversity, soluble factors secreted by host and microbe, as well as host immune system, all contribute to both the physical and immunologic aspects of the FGT mucosal barrier. Current gaps in what is known about the effects of the microbiome on FGT mucosal barrier function are compared and contrasted with the literature of the gut and respiratory mucosa. This review article presents evidence supporting that the vaginal microbiome, directly and indirectly, contributes to how well the FGT protects against infection.